1997
DOI: 10.1093/clinchem/43.6.1010
|View full text |Cite
|
Sign up to set email alerts
|

Determination of d-lactate by enzymatic methods in biological fluids: study of interferences

Abstract: Analysis of nondeproteinized samples with an enzymatic method to determine d-lactate indicated interferences. The presence of l-lactate dehydrogenase (LD) and l-lactate in the sample led to underestimation of d-lactate content when a sample blank was processed and overestimation when it was omitted. We proved that this interference is not due to lack of d-LD stereospecificity. Moreover, assessment of d-LD and l-LD KM for NAD+ allowed us to rule out the different affinities for this coenzyme as a cause of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…Several methods have been reported to measure d ‐lactate concentrations in body fluids . The d ‐lactic acid spectrophotometer assay is the most widely used and should be easily adaptable for use in most clinical laboratories as it is simple to perform and only requires a d ‐lactate assay kit and a spectrophotometer.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Several methods have been reported to measure d ‐lactate concentrations in body fluids . The d ‐lactic acid spectrophotometer assay is the most widely used and should be easily adaptable for use in most clinical laboratories as it is simple to perform and only requires a d ‐lactate assay kit and a spectrophotometer.…”
Section: Discussionsupporting
confidence: 55%
“…A commercial d ‐lactate analysis kit (Megazyme International, Wicklow, Ireland) was used according to the manufacturer's recommendations . All calculations were made automatically by the analyzer's software (Mega‐Calc.…”
Section: Methodsmentioning
confidence: 99%
“…The use of colorimetric assays however is commonplace in human medicine and in other studies of mammals with results that are comparable to HPLC measurements. 18,[29][30][31][32][33] A recent study using the modified strong ion model in CPV dogs confirmed that acid-base disturbances in this population are multifactorial, with chloride playing an important role in acid-base changes. 34 Our study identified intermittent correlation of D-lactate to multiple acidbase markers, most notably at admission, but no consistent trends were appreciated throughout hospitalization.…”
Section: Methodsmentioning
confidence: 89%
“… 15 SF and blood samples defrosted at room temperature and then centrifuged using polyethersulfone ultrafiltration membranes (Fisher Scientific, Leicester, UK) at 4000 g for 10 minutes to improve test accuracy. 23 A value of 0 was used for measurements below the limit of detection (0.21 µg/ml).…”
Section: Methodsmentioning
confidence: 99%